2005
DOI: 10.1002/tl.184
|View full text |Cite
|
Sign up to set email alerts
|

Teaching statistics by taking advantage of the laptop's ubiquity

Abstract: This chapter reports on a mathematics professor's experience leveraging laptops in a required intermediate statistics course with a challenging student population.Use of laptops streamlined course delivery, enhanced classroom interaction, and improved both his students' and his own overall course experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Since technology provides a compelling source of interactive tools for academic purposes ranging from taking notes, participation in discussion forums, access to supplementary resources, software and applications and facilitate student-student and student-faculty interactions, it may foster engagement and selfdirected learning (Fried, 2008;Hyden, 2005;Juniu, 2006;Rust, O'Donovan, & Price, 2005;Weaver & Nilson, 2005;White & Robertson, 2014;Williams, Karousou, & Mackness, 2011). Students who use information technology for academic purposes are reported to more likely contribute and participate in active, academic collaboration with other students (Nelson Laird & Kuh, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Since technology provides a compelling source of interactive tools for academic purposes ranging from taking notes, participation in discussion forums, access to supplementary resources, software and applications and facilitate student-student and student-faculty interactions, it may foster engagement and selfdirected learning (Fried, 2008;Hyden, 2005;Juniu, 2006;Rust, O'Donovan, & Price, 2005;Weaver & Nilson, 2005;White & Robertson, 2014;Williams, Karousou, & Mackness, 2011). Students who use information technology for academic purposes are reported to more likely contribute and participate in active, academic collaboration with other students (Nelson Laird & Kuh, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…The aforementioned roles of multimedia software and its accessibility have furnished its result to be used recurrently in the classroom. Although, there is extensive debate about the efficacy of laptop computers in the classroom, several studies have identified benefits such as keeping students on task and engaged (Hyden, 2005), and helping students follow lectures via PowerPoint or multimedia (Lauricella & Kay, 2010).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…First, the predominant method of data collection is the case study (Weaver, 2005;Weaver & Nilson, 2005;Hyden, 2005;Birrenkott, Birtrand & Bolt, 2005;Brown, 2005;Granberg & Witte, 2005;Ohland & Stephan, 2005;Pargas & Weaver, 2005;Stephens, 2005;McVay, Snyder & Graetz, 2005). While this approach offers guidance and advice on best practices for using laptops, the reliability and validity of the data have yet to be confirmed for the general population.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Several studies have identified benefits such as keeping students on task and engaged (Hyden, 2005), or following lectures via PowerPoint or multimedia (Debevec, Shih & Kashyap, 2006). However, other research indicates that using laptops in class can be a disadvantage (Fried, 2008).…”
Section: Overviewmentioning
confidence: 99%